Multiphase composite coatings: structure and properties; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Yurov V. M.; Guchenko S. A.; Platonova E. S.; Syzdykova A. Sh.; Lysenko E. N. Elena Nikolaevna (2015, 2015)
Title screen